Do Multiple Time Consumers also Observe Imperfectly?:The Case of Automobile Consumers in India - Chattopadhyay, Tanmay; Shivani, Shraddha; Krishnan, Mahesh (Indian Journal of Marketing, 2009)
Consumer learning about quality of alternate brands of an experienced good may occur through several mechanisms. Increased attention has been focused on the nature of brand equity and on its role on improving market performance or financial success of products whose names influence the level of consumer acceptance (Aakar 1991). General observation on the importance of brand equity to marketing and financial results has also been discussed in the literature (Farquhar, 1989). Again scattered empirical studies have answered such questions as impact of brand equity on the success of line and category extensions designed to trade on the cachet of a brand name (Aakar and Keller, 1990). The challenge of measuring brand equity lies in the fact that numerous alternative approaches exist (Chattopadhyay, Shivani and Krishnan, 2008) but all such methods appear to be inherently imperfect (Shocker, 1991). In this paper, we estimate a dynamic choice model in which consumers correlate brand quality through price signals.